“I don't know if she likes reading”: Are teachers perceived to be keen readers, and how is this determined? - Merga, Margaret (2016)
© 2016 National Association for the Teaching of English The benefits of regular recreational reading for literacy development have been widely acknowledged, and as such, encouraging children to be life-long readers is an educational imperative. Teachers who are models of keen recreational reading can play an important role in fostering a keen love of reading in children, so that they regularly engage in the practice. However, it is not known if all teachers have the time, inclination and awareness to actively model a love of reading in their classrooms. This article explores data from the 2016 Western Australian Study in Children's Book Reading to ascertain which teacher behaviours and attitudes children deem indicative of a love of reading. While many children did not know if their teachers liked reading or not, teachers who were perceived to be readers talked about books in the context of pleasure, were seen to read independently at school, and read aloud to the class with expression and emotional connection.